Surgical treatment of patients with myelomeningocele-related spine deformities: study of 26 cases - SARAÇOĞLU, AYTEN (SPRINGER, 2018)
Scoliosis, kyphosis, and sacral agenesis (SA) are common spine deformities in myelomeningocele (MMC) patients. Surgery of spine deformities in MMC patients is associated with various difficulties as infection, pathological skin breakage, instrumentation failure, and neurological deterioration. The purposes of this study are to share our clinical experience and discuss different surgical techniques which are defined in the literature. We retrospectively evaluated our database of patients with MMC who underwent surgical procedures for spine deformities from 2014 to 2016. Demographic and clinical data, surgical parameters, surgical techniques and levels, pre- and postoperative deformity angles, level of posterior fusion defect, spinal malformations, neurological evaluation of lower extremities and complications were collated. We divided the cases into three groups according to the type of deformities. The groups were lumbar kyphosis (Group 1), congenital scoliosis (Group 2), and paralytic scoliosis (Group 3). There were 26 patients in the study. Fifteen patients were male and 11 patients were female. The median age of the patients was 8.03 (range = 3-17 years) at the time of operation. There were 10 patients in Group 1, 7 patients in Group 2, and 9 patients in Group 3. In Group 1, preoperative kyphosis angle varied between 51A degrees and 160A degrees, with an average of 95.7A degrees. In Group 2, preoperative Cobb angle varied between 57A degrees and 150A degrees, with an average of 106.6A degrees. Kyphosis was present in 4 patients. Preoperative kyphosis angle varied between 74A degrees and 140A degrees, with an average of 93A degrees. In Group 3, preoperative Cobb angle varied between 45A degrees and 145A degrees, with an average of 72.5A degrees. Spinal deformity in children with MMC has been considered to cause severe disability. Surgical treatment is a challenging procedure with a wide spectrum of complications, but can provide good correction of spinal deformity and pelvic obliquity, and improve the quality of life. Self-growing systems which are a new alternative to traditional growing rod systems, must be considered to preserve growing potential of spine.
Keywords: Kyphosis; Myelomeningocele; Sacral agenesis; Scoliosis; GROWING ROD; CORD TRANSECTION; SACRAL AGENESIS; SCOLIOSIS; KYPHECTOMY; MANAGEMENT; EFFICACY; SAFETY